An introduction to geological structures & maps - Stawikowski, Wojciech (Geologos, 2025)
An introduction to geological structures & maps, by G.M. Bennison, P.A. Olver & K.A. Moseley, 2017. Routledge, New York/London, 184 pages. Hardback: price GBP 120.00, ISBN 978-1-03232015-1.